Çok Damarlı ST Yükselmesiz Miyokard İnfarktüsü Hastalarında Tek Aşamalı ve Çok Aşamalı Koroner Revaskülarizasyonun Mortalite Sonuçları - Gökhan Alıcı; Omer Genc; Hazar Harbalıoğlu; Abdullah Yıldırım; Örsan Deniz Urgun; Mustafa Gür; Alaa Quisi; Samir Allahverdiyev (Düzce Tıp Fakültesi Dergisi, 2021)
Aim: The aim of this study was to compare the short-term and long-term mortality results of single-stage percutaneous coronary intervention (SS-PCI) and multi-stage percutaneous coronary intervention (MS-PCI) strategies in patients diagnosed with non-ST segment elevation myocardial infarction (NSTEMI) with multivessel disease. Material and Methods: A total of 298 consecutive patients diagnosed with multivessel NSTEMI (71 (23.8%) patients in the SS-PCI group and 227 (76.2%) patients in the MS-PCI group) were included in this study. Data regarding mortality were obtained from the health information system of our institute and national health registry. Results: Although in-hospital mortality rates were found to be significantly higher in univariate analysis in the SS-PCI group compared to the MS-PCI group (14.1% (n=10) vs 4.0% (n=9); p=0.005), it was not independently associated with total mortality in multiple model. Among the parameters predicted mortality determinants, low hemoglobin (odds ratio (OR)=0.485, 95% confidence interval (CI)=0.332-0.708; p=0.002), No-reflow occurrence (OR=6.194, 95% CI=1.310-29.300, p=0.021), not using post dilatation (OR=0.287, 95% CI=0.085-0.970, p=0.045) were independently associated with total mortality. Conclusion: There was no statistical difference in overall mortality between the two study groups in multivessel NSTEMI patients who underwent complete coronary revascularization with the SS-PCI and MS-PCI strategy, while low hemoglobin, No-reflow phenomenon, and not using post-dilatation were found as independent predictors of mortality.